HUBUNGAN PEMANFAATAN TEKNOLOGI DENGAN KECERDASAN SPIRITUAL PERAWAT DI RUMAH SAKIT SANTA ELISABETH MEDAN - Lindawati Simorangkir; Lilis Novitarum; Titin Dwijayanti Situmorang (Elisabeth Health Jurnal, 2020)
Background : Nurses who are spiritually intelligent are able to positionbehavior, assess health measures given, be able to place feelings andface busy work and try to be responsible at work. Reducing workdensity, nurses take advantage of technology that can providechanges in terms of helping work, communication and so on so thatthe nurse's time to patients is moreMethods: The study design used an analytic survey design with cross sectionalmethod. Sampling using probability sampling with a Systematicsampling technique with a sample size of 58 people. The instrumentused in this study was a questionnaireResults: The results showed that the use of nurse technology was good(94.8%), the spiritual intelligence of nurses was high (58.6%).Elisabteh Health Journal : Jurnal Kesehatan, Vol. V No. 02 (Desember, 2020) : V-02 E-ISSN 2541-4992Discussion: In hospital services nurses must be able to utilize existingtechnology as reformers and be competitive in the world of healthand be able to place spirituality: their feelings and emotions inproviding nursing care to ensure an increase in the quality ofhospital services